Contribution of the serine kinase c-Jun N-terminal kinase (JNK) to oxidant-induced insulin resistance in isolated rat skeletal muscle - Santos,F.R. (Informa Healthcare, 2015)
The specific and direct contribution of the stress-activated serine kinase c-Jun N-terminal kinase (JNK) in the development of oxidative stress-induced insulin resistance of the glucose transport system in mammalian skeletal muscle is not fully understood. We assessed the specific role of JNK in the development of insulin resistance caused by in vitro exposure of rat soleus muscle to low levels (30-40 μM) of the oxidant hydrogen peroxide (H2O2) for up to 6h. Oxidant exposure caused significant (p < 0.05) decreases in insulin-stimulated glucose transport activity (up to 42%) and Akt Ser 473 phosphorylation (up to 67%), and increased (up to 74%) phosphorylation (Thr183/Tyr185) of JNK1 and JNK2/3 isoforms. Importantly, insulin-stimulated glucose transport activity in the presence of H2O2 was moderately improved with the selective JNK inhibitor SP600125. These results indicate that activation of the serine kinase JNK contributes, at least in part, to oxidative stress-induced insulin resistance in isolated mammalian skeletal muscle. © 2012 Informa UK, Ltd.